Electrical and Crystallographic Study of an Electrothermodynamic Cycle for a Waste Heat Recovery. (16th August 2018) - Kim, Juyoung; Yamanaka, Satoru; Nakajima, Akira; Katou, Takanori; Kim, Juyoung; Kim, Yoonho; Fukuda, Tatsuo; Yoshii, Kenji; Nishihata, Yasuo; Baba, Masaaki; Takeda, Masatoshi; Yamada, Noboru; et al.
Abstract: For decades, wasted heat has increased, and the thermal energy conversion system has become more important, especially in automobile applications. For waste heat recovery, an innovative electrothermodynamic cycle (pyroelectric effect with an external electric field) was recently presented, which is based on temporal temperature variations in wasted heat from engine exhaust gas. Herein, for further improvement, a generating mechanism of the cycle is investigated via an Operando analysis, time‐resolved synchrotron X‐ray diffraction with generating assessment. Polarization changes are analyzed via simultaneous electrical and crystallographic studies. Three types of materials are prepared: soft and hard types of PZTs and lead magnesium niobate—lead titanate (PMN‐PT). Among them, PMN‐PT has the highest generating power. When an external electric field is applied, the PMN‐PT exhibits only 180° domain rotations, whereas the other materials exhibit both 90° and 180° rotations. A strong driving force for 180° rotation depresses rotations in other angles and increases polarization changes. The results show that the material development, which has only 180° switching domains, has potential for use in the establishment of a high‐efficiency waste heat recovery system. Abstract : Here, the generating mechanism of an original electrothermodynamic cycle is presented by electrical and crystallographic studies using the Operando analysis, time‐resolved synchrotron X‐ray diffraction with a generating assessment. As a result, the domain organization on pyroelectric material is confirmed as the key for the high generating performance. Further development of materials with more 180° domain switchings grant the waste heat recovery system a higher efficiency.